2016
DOI: 10.5194/bg-13-3359-2016
|View full text |Cite
|
Sign up to set email alerts
|

The status and challenge of global fire modelling

Abstract: Abstract. Biomass burning impacts vegetation dynamics, biogeochemical cycling, atmospheric chemistry, and climate, with sometimes deleterious socio-economic impacts. Under future climate projections it is often expected that the risk of wildfires will increase. Our ability to predict the magnitude and geographic pattern of future fire impacts rests on our ability to model fire regimes, using either well-founded empirical relationships or process-based models with good predictive skill. While a large variety of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
333
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 364 publications
(340 citation statements)
references
References 107 publications
(141 reference statements)
6
333
0
1
Order By: Relevance
“…The improvements that were made here reinforce the idea that aside from "top-down" climate control on fire activity, other factors such as lightning, fuel availability, and composition can influence fire statistics (Podur et al, 2002). This highlights the necessity of reconstructing fire history in a complex system that is related to climate and vegetation by taking into account several feedbacks (Hantson et al, 2016).…”
Section: Agreements and Disagreements In Fire Activity And Forest Growthsupporting
confidence: 62%
See 4 more Smart Citations
“…The improvements that were made here reinforce the idea that aside from "top-down" climate control on fire activity, other factors such as lightning, fuel availability, and composition can influence fire statistics (Podur et al, 2002). This highlights the necessity of reconstructing fire history in a complex system that is related to climate and vegetation by taking into account several feedbacks (Hantson et al, 2016).…”
Section: Agreements and Disagreements In Fire Activity And Forest Growthsupporting
confidence: 62%
“…The use of a high-quality lightning strike data set instead of the low-resolution LIS/OTD global data set that was used by Pfeiffer et al (2013) allowed us to capture the spatial gradient of fire activity in a substantially better manner (Baker et al, 2016). The results confirmed that fire in the study area is strongly ignition limited, while most fire models have simply assumed that fire would always occur under appropriate weather and fuel conditions, e.g., SIMFIRE (Hantson et al, 2016). LPJ-LMfire simulations confirmed the necessity of simulating fire in a model as the product of the probabilities that are associated with fuel, moisture and ignition.…”
Section: Agreements and Disagreements In Fire Activity And Forest Growthmentioning
confidence: 64%
See 3 more Smart Citations